THE DYNAMICS OF POLITICAL CONSCIOUSNESS IN NAYANTARA SAHGAL’S THIS TIME OF MORNING (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the theme of political consciousness in Nayantara Sahgal’s This Time of Morning, a novel set in the early years of post-independence India. The narrative offers a critical exploration of the political awakening among the Indian elite as they navigate the complex realities of newfound independence. Sahgal’s characters, drawn from the upper echelons of society, grapple with the challenges of power, moral ambiguity, and the expectations of nation-building. The paper argues that Sahgal’s portrayal of political consciousness is deeply intertwined with the personal journeys of her characters, who are often caught between idealism and pragmatism. The novel reflects the disillusionment that many felt as the promises of independence gave way to the harsh realities of governance, social inequality, and corruption. Through close textual analysis, this paper highlights how Sahgal critiques the dissonance between the lofty ideals of the freedom movement and the actual practices of those in power.